2015
DOI: 10.4103/1319-3767.151228
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum galectin-3 levels in patients with hepatocellular cancer and chronic viral hepatitis

Abstract: Background/Aim:Galectins affect diverse physiological and pathophysiological processes such as development, inflammation, and tumor growth. We aimed to compare serum galectin-3 levels in three patient groups with chronic hepatitis B and C virus (HBV, HCV), cirrhosis secondary to HBV or HCV, and hepatocellular carcinoma (HCC) secondary to HBV or HCV and evaluate the role of galectin-3 during HCC progression.Patients and Methods:Nineteen patients with hepatocellular cancer, 22 patients with cirrhosis, and 24 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…Previous studies have revealed an elevated concentration of serum galectin-3 in various cancers, including breast (20), colorectal (21,22), stomach (23), lung (20), bladder (24), head and neck (25), liver (26), thyroid (27), pancreatic (28) and melanoma (29). These studies demonstrated higher amounts of galectin-3 in the sera of patients and its association with poorer prognosis.…”
Section: Introductionmentioning
confidence: 63%
“…Previous studies have revealed an elevated concentration of serum galectin-3 in various cancers, including breast (20), colorectal (21,22), stomach (23), lung (20), bladder (24), head and neck (25), liver (26), thyroid (27), pancreatic (28) and melanoma (29). These studies demonstrated higher amounts of galectin-3 in the sera of patients and its association with poorer prognosis.…”
Section: Introductionmentioning
confidence: 63%
“…Galectin-3 is the most extensively studied. Oncogenic and viral stimulation can change galectin-3 expression and galectin-3 increases in several human tumors (11) . Normal hepatocytes do not express galectin-3, but this protein can be present in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-3, a beta-galactoside binding lectin, is a moonlighting protein, implicated in cell growth, differentiation, apoptosis, adhesion, malignant transformation, RNA processing, and angiogenesis [1][2][3][4][5] . Accumulating evidence has revealed an elevated concentration of serum galectin-3 in various cancers including breast 6) , colorectal 7,8) , stomach 9) , lung 6) , bladder 10) , head and neck 11) , liver 12) , thyroid 13) , pancreatic 14) , and melanoma 15) . These studies demonstrated higher amounts of galectin-3 in the sera of patients and/or its association with their prognosis.…”
Section: Introductionmentioning
confidence: 99%